1997
DOI: 10.1038/sj.onc.1201464
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 inhibits p53 nuclear import following DNA damage

Abstract: Bcl-2 is an integral membrane oncoprotein that localizes to membranes of the mitochondria, endoplasmic reticulum, and nuclear envelope. Bcl-2 is a member of a family of cell death regulators and functions to inhibit apoptosis. Using confocal microscopy and immunoblotting we show that the ability of bcl-2 to suppress cell death following genotoxic damage can be a consequence of inhibiting nuclear import of induced wild-type p53 protein. Our data suggests that the ability of bcl-2 to modulate tra cking events is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
3
4

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 27 publications
0
44
3
4
Order By: Relevance
“…RT4 was used as a positive control because we have demonstrated, using antisense, that Bcl-2 protects against drug-induced apoptosis in this cell type (Arriola, manuscript in preparation). Recently, Bcl-2 has been shown to inhibit translocation of p53 to the nucleus and this has been suggested to be important for function (Beham et al, 1997). However, we did not ®nd this to be the case in either RT4, where Bcl-2 inhibits apoptosis ( Figure 3i) or in 833K.Bcl-2 clones, where Bcl-2 promotes apoptosis ( Figure 3f).…”
Section: Overexpression Of Bcl-2 Enhances Etoposide-induced Apoptosiscontrasting
confidence: 46%
“…RT4 was used as a positive control because we have demonstrated, using antisense, that Bcl-2 protects against drug-induced apoptosis in this cell type (Arriola, manuscript in preparation). Recently, Bcl-2 has been shown to inhibit translocation of p53 to the nucleus and this has been suggested to be important for function (Beham et al, 1997). However, we did not ®nd this to be the case in either RT4, where Bcl-2 inhibits apoptosis ( Figure 3i) or in 833K.Bcl-2 clones, where Bcl-2 promotes apoptosis ( Figure 3f).…”
Section: Overexpression Of Bcl-2 Enhances Etoposide-induced Apoptosiscontrasting
confidence: 46%
“…Some studies have shown that RT decreases Bcl-2 protein expression in p53 wild-type cell lines, in conjunction with apoptotic cell death (26); p53 appears to down-regulate the expression of bcl-2 and transactivate bax (27). Moreover, Bcl-2 appears to inhibit the nuclear transport of p53 in response to genotoxic stress (28). In cell lines lacking wild-type p53 protein, bcl-2 expression may be up-regulated by RT (29).…”
Section: Discussionmentioning
confidence: 99%
“…The failure of bcl-2 to protect against prostate carcinoma cell death induction resulting from inhibition of proteasomal activity is noteworthy in that bcl-2 expression has been shown to confer resistance to prostate cell death induction by divergent stresses including g-radiation, p53, ceramide, inhibitors of arachidonate metabolism, TNF-a, and androgen deprivation in an orthotopic animal model system (Beham et al, 1997;Herrmann et al, 1997a,b;Tu et al, 1995;Westin et al, 1997). Several possibilities might account for the inability of bcl-2 to protect against proteasome inhibitors.…”
Section: Discussionmentioning
confidence: 99%